2017
DOI: 10.1111/1471-0528.14534
|View full text |Cite
|
Sign up to set email alerts
|

Hyperemesis gravidarum and cardiometabolic risk factors in adolescents: a follow‐up of the Northern Finland Birth Cohort 1986

Abstract: Hyperemesis gravidarum does not affect cardiometabolic health in adolescent offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
0
12
1
Order By: Relevance
“…(13)(14)(15)(16) None of these studies found differences in offspring lipid concentrations in childhood. (13)(14)(15)(16) Two studies however, did find that offspring born to women with HG were heavier and more adipose in childhood than offspring born to women without HG, (14,16) which can in line lead to increased Apo-B levels in later life, and therefore affect offspring cardiovascular disease risk. (43) Taking our findings into account, differences in these studies' findings might be due to differences in HG severity with studies including women with a more severe HG being more likely to find associations than studies including women with a relatively mild HG.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…(13)(14)(15)(16) None of these studies found differences in offspring lipid concentrations in childhood. (13)(14)(15)(16) Two studies however, did find that offspring born to women with HG were heavier and more adipose in childhood than offspring born to women without HG, (14,16) which can in line lead to increased Apo-B levels in later life, and therefore affect offspring cardiovascular disease risk. (43) Taking our findings into account, differences in these studies' findings might be due to differences in HG severity with studies including women with a more severe HG being more likely to find associations than studies including women with a relatively mild HG.…”
Section: Discussionmentioning
confidence: 97%
“…(12) In the limited literature available on the topic of long term effects of HG on offspring, a wide range of HG definitions and outcomes were employed, and little information was collected on the role of maternal nutrition. (13)(14)(15)(16) This is of particular relevance as nutritional supplementation is not generally included in HG clinical management plans. (17) The role of maternal nutrition in HG, or the role of HG disease severity on offspring health in later life has not been investigated, nor has the ability of nutritional supplementation to amend such effects.…”
Section: Introductionmentioning
confidence: 99%
“…The psychological distress appears to be self-limiting in tandem with symptoms of HG [3]. Koot and colleagues (2017) [25] examined physical data in an attempt to predict whether BMI affected the HG phenomenon, but found no significant proof. However, they did show that suffering from HG would affect the pregnant woman's BMI, whether by gaining very little weight or no weight at all during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…7 For the male fetus, association with an increase in premature risk and neonatal morbidity is found. 33 It should be noted that the percentage of HG incidence in female and male fetuses didn't show a significant difference. 19,28,31,33 There is an association between HG and a heavier weight of the placenta compared with birth weight.…”
Section: Incidence a N D Risk Factorsmentioning
confidence: 92%
“…There was no association between HG and the longterm mortality of the fetus, as well as the risk of cardiovascular disease during adolescence. 33,40 In conclusion, HG is a complex, multifactorial condition with many potential etiological factors. 39…”
Section: Incidence a N D Risk Factorsmentioning
confidence: 99%